A review article on: Voltammetric detection of lead, mercury, chromium, and arsenic metal ions from environmental samples - Andualem Ejigu; Molla Tefera; Atnafu Guadie (Electrochemistry Communications)
Detecting hazardous heavy metals like lead, cadmium, mercury, and arsenic is a significant global issue because of their high toxicity and environmental durability. While traditional laboratory methods provide accurate results, their high cost, complexity, and slow processing times restrict their practicality for widespread, on-site monitoring. In this regard, electrochemical techniques, especially voltammetry, have become a strong alternative, delivering a great mix of high sensitivity, portability, and affordability.This review highlights recent advancements in innovative electrode materials, such as graphene-modified electrodes and sensors enhanced with metal nanoparticles, along with advanced stripping techniques like anodic stripping voltammetry (ASV) and square wave voltammetry (SWV). Thanks to these advancements, detection limits have improved significantly, often reaching the parts per billion (ppb) range, while the selectivity for specific metal ions has also been enhanced.Additionally, the review critically examines methods for analyzing water, soil, and sediment samples, showcasing the promising capabilities of nanocomposite materials that greatly increase sensitivity and stability. It also emphasizes the importance of standardized protocols for reliable comparisons and discusses future research directions, including the development of new nanocomposite materials and the integration of these advanced ‘nanosensors’ into portable devices for real-time environmental monitoring.